Ataxia-telangiectasia and combined hepatocellular-cholangiocarcinoma: A case report - Tej P Singh; Shraddha Patkar; Mahesh Goel; Munita Bal Menon (Indian Journal of Pathology and Microbiology, 2023)
Ataxia-telangiectasia (A-T) is a rare autosomal recessive disease characterized by ataxia, cutaneous and ocular telangiectasia, impaired immunity with susceptibility to sino-pulmonary infections, radiation sensitivity, and cancers particularly of hemato-lymphoid origin. Liver function tests abnormalities and elevated alfa feto-protein have been reported in A-T; however, there is no reported case of combined hepatocellular-cholangiocarcinoma (cHCC-CC) in literature. These tumors should be treated in similar fashion as in general population; however, reduction of chemotherapy dose might be helpful in decreasing chemo-toxicity.